Grain size effect on multi-scale fatigue crack growth mechanism of Nickel-based alloy GH4169. (July 2015) - Qin, Cheng-Hua; Zhang, Xian-Cheng; Ye, Shen; Tu, Shan-Tung
Highlights: Mechanism of multi-scale fatigue crack propagation of Nickel-bases alloy GH4169 was identified. Specimen with coarser grain exhibited longer fatigue life. Small fatigue crack stage accounted for an obvious fraction of the total fatigue life. Fatigue crack would propagate through three stages. An empirical formula was obtained to predict the small crack growth rate. Abstract: The mechanism of multi-scale fatigue crack propagation of Nickel-bases alloy GH4169 with different grain sizes was identified in this paper by using the specimens with micro-notches. Results showed that specimen with coarser grain exhibited longer fatigue life. Grain size effect on the growth rate of small crack cannot be distinguished due to the fluctuation of crack growth rate. The small fatigue crack stage accounted for a larger fraction of the total fatigue life for the specimen with finer grain size. An empirical formula was proposed to predict the relationship between the growth rate of small crack and crack length.